2015
DOI: 10.1016/j.schres.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Working memory impairment in probands with schizoaffective disorder and first degree relatives of schizophrenia probands extend beyond deficits predicted by generalized neuropsychological impairment

Abstract: Objective Working memory impairment is well established in psychotic disorders. However, the relative magnitude, diagnostic specificity, familiality pattern, and degree of independence from generalized cognitive deficits across psychotic disorders remain unclear. Method Participants from the Bipolar and Schizophrenia Network on Intermediate Phenotypes (B-SNIP) study included probands with schizophrenia (N=289), psychotic bipolar disorder (N=227), schizoaffective disorder (N=165), their first-degree relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…First, both SZ and BP showed increased brain signal randomness in vlPFC, a brain region that is associated with the selection and maintenance of goal-relevant item information (Blumenfeld et al, 2013), and SAD and BP showed increased brain signal randomness in vmPFC, a brain region that is associated with social decision making (van den Bos and Guroglu, 2009), theory of mind (Leopold et al, 2012), as well as generating (Koenigs et al, 2007) or regulating emotions (Koenigs et al, 2007; Phillips et al, 2008; Ritter et al, 2004). Although we did not find the consistent patterns of correlations between increased brain signal randomness and psychopathology, the overlap between SAD and BP in vmPFC may explain the clinical similarity of mood dysregulation exhibited in both disorders, and the overlap between SZ and BP in vlPFC may be associated with reduced working memory commonly seen in the broader category of psychotic disorders (Glahn et al, 2005; Hill et al, 2015). …”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…First, both SZ and BP showed increased brain signal randomness in vlPFC, a brain region that is associated with the selection and maintenance of goal-relevant item information (Blumenfeld et al, 2013), and SAD and BP showed increased brain signal randomness in vmPFC, a brain region that is associated with social decision making (van den Bos and Guroglu, 2009), theory of mind (Leopold et al, 2012), as well as generating (Koenigs et al, 2007) or regulating emotions (Koenigs et al, 2007; Phillips et al, 2008; Ritter et al, 2004). Although we did not find the consistent patterns of correlations between increased brain signal randomness and psychopathology, the overlap between SAD and BP in vmPFC may explain the clinical similarity of mood dysregulation exhibited in both disorders, and the overlap between SZ and BP in vlPFC may be associated with reduced working memory commonly seen in the broader category of psychotic disorders (Glahn et al, 2005; Hill et al, 2015). …”
Section: Discussioncontrasting
confidence: 86%
“…A recent systematic review of cognition in SZ and BP found that overall both SZ and BP patients present deficits on all neurocognitive measures compared to healthy controls (Hill et al, 2015; Hill et al, 2013; Vohringer et al, 2013). In particular, SZ patients showed more severe and pervasive cognitive deficits while BD patients present a milder and more confined impairment.…”
Section: Discussionmentioning
confidence: 99%
“…One feature is cognitive impairment (26), which is present before disease onset (7), reasonably stable throughout the course of illness (810), and predicts functional outcome (11, 12). The range of cognitive impairment observed in patients with psychotic disorders includes disruptions in behavioral inhibition, working memory, context processing, problem solving and reasoning, processing speed, and verbal memory (1318). Another feature is structural brain abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psychosis experience a general cognitive deficit, and it is sometimes unclear whether a between-group difference in performance on a particular task is driven by a specific or the general deficit (e.g., Reilly et al 2016; Reilly and Sweeney 2014; Kristian Hill et al 2015). Many previous studies have assumed that WM is specifically disrupted in psychosis (Forbes et al 2009; Lee and Park 2005; Piskulic et al 2007).…”
Section: Discussionmentioning
confidence: 99%